To solve the equation \( x^2(2x-1) + 3x(2x-1) - 4(2x-1) = 0 \), we can factor out the common term \( (2x-1) \):
\[ (2x-1)(x^2 + 3x - 4) = 0 \]
This gives us two equations to solve:
- \( 2x - 1 = 0 \)
- \( x^2 + 3x - 4 = 0 \)
Starting with the first equation:
\[ 2x - 1 = 0 \Rightarrow 2x = 1 \Rightarrow x = \frac{1}{2} \]
Next, we solve the second equation \( x^2 + 3x - 4 = 0 \). To factor this quadratic equation, we look for two numbers that multiply to \(-4\) and add to \(3\). The numbers \(4\) and \(-1\) work because:
\[ 4 + (-1) = 3 \quad \text{and} \quad 4 \cdot (-1) = -4 \]
Thus, we can factor the equation as follows:
\[ (x + 4)(x - 1) = 0 \]
Setting each factor equal to zero gives:
\[ x + 4 = 0 \Rightarrow x = -4 \]
\[ x - 1 = 0 \Rightarrow x = 1 \]
So the complete set of solutions from the two equations is:
\[ x = \frac{1}{2}, \quad x = -4, \quad x = 1 \]
Now we can compile the complete set of solutions:
\[ x = \frac{1}{2}, -4, 1 \]
Thus, the complete set of solutions to Janet's equation is \(\frac{1}{2}, -4, 1\). According to the response options provided, this corresponds to:
\(\frac{1}{2}, -4, 1\) (hidden in the format used).
So the answer is:
\(\frac{1}{2}, -4, 1\)